The Role of Islamic Religious Education Teachers in Developing Effective Learning Resources at Muhammadiyah Vocational Schools - Uswatun Khasanah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Letiges & Association of Muslim Community in ASEAN (AMCA), 2022)
This study aims to identify and analyze the process of developing and managing learning resources by Islamic Religious Education teachers at SMK Muhammadiyah Delanggu, Klaten, Central Java, Indonesia. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that teachers have developed various learning resources that are innovative and relevant to students' needs. Teachers and schools collaborate effectively to manage learning resources, and they utilize information technology to enhance the learning process. The obstacles faced include limited resources and a lack of training for teachers. The proposed solution is to improve school facilities and organize routine training for teachers.